1998
DOI: 10.3759/tropics.8.31
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Distribution of Soils at Lambir Hills National Park in Sarawak, Malaysia, with Special Reference to Soil Hardness and Soil Texture.

Abstract: For the rehabilitation of the degraded and abandoned land in the tropical area, it needs to define the various characteristics of remaining natural forests. This work was done to find out a physical hazard for root elongation of plant at Lambir Hills National Park, Miri, Sarawak, Malaysia, with special reference to soil hardness and soil texture. Furthermore, soil moisture and soil temperature were monitored at the hill ridge and at the valley to show their annual fluctuation. Soil physico-chemical properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 10 publications
(8 reference statements)
5
39
1
Order By: Relevance
“…According to Table 10, the phosphorus availability in the soil decreased with depth. A similar result has been reported by Hirai et al (1997) and Ishizuka et al (1998). The concentration of organic matter may play an important factor due to surface of the soils have higher organic matter.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…According to Table 10, the phosphorus availability in the soil decreased with depth. A similar result has been reported by Hirai et al (1997) and Ishizuka et al (1998). The concentration of organic matter may play an important factor due to surface of the soils have higher organic matter.…”
Section: Discussionsupporting
confidence: 76%
“…The result of soil profile in Table 10 showed that the content of organic matter declined with increasing depth. According to Ishizuka et al (1998), organic matter content in the surface horizon was high due to development of root mats.…”
Section: Discussionmentioning
confidence: 99%
“…The similar results have been reported by others (Ishizuka et al 1998;Akbar et al 2010). Lower amounts of available P in the subsoils of the three land uses studied might be ascribed to the lower amount of organic matter and higher fixation of phosphorus in subsoils.…”
Section: Soil Chemical Characteristicssupporting
confidence: 80%
“…SOM in the surface soils was higher than the subsurface soils. According to Ishizuka et al (1998), organic matter content was high in the surface due to the development of roots mats and accumulation of forest litter.…”
Section: Ajesmentioning
confidence: 99%
“…However, the composition of forest floor also plays an important role in P contents. Organic matter may be a factor due to higher organic matter in the surface soil (Hirai et al, 1997;Ishizuka et al, 1998).…”
Section: Ajesmentioning
confidence: 99%